Intensity of Work-Family Conflict and Its Impact on Female Nurses Performance - Sutisna, Deden; Ismail, Solahuddin; Putri, Silfia Ayu (Universitas Brawijaya, Indonesia, 2024)
This research is an important finding because it will reveal the intensity of conflict between female workers and their families during COVID-19, as well as the subsequent impact on the performance of female nurses who are married. The study aimed to determine the conditions and contribution of women's work-family conflict to the performance of married female nurses at the Otto Iskandar Dinata Hospital, Bandung, West Java. This research was conducted when COVID-19 had been going on for 3 years. At that time all sectors were affected, especially the local government's public health service units which had direct access to handling the COVID-19 pandemic, which involved workers from various health professions who were inseparable from conflicts in their work and families. The research method used is causal associative, qualitative, and quantitative data types. The data collection method is by literature study and field study, while the data collection techniques use observation, interviews, and questionnaires. Data analysis was assisted by statistical software SPSS version 25 with multiple linear regression analysis, correlation coefficient, and coefficient of determination. The study population consisted of 148 female nurses, and 69 were taken as a sample, with 80 data taken from the field. The results showed that the General demands of a role and Time devoted to a given role conditions had a relatively high conflict intensity, and the Strain produced by a given role condition had a high conflict intensity, while the performance condition had a very good level. Work-family conflict has a small effect on performance, and the effect is significant. The results of this study hoped that the regional government health service organization will be able to determine work policies for female nurses so that the workload is distributed evenly and there is no high conflict intention, which results in decreased performance.